2016
DOI: 10.1371/journal.pone.0157273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transducer Orientation on Errors in Ultrasound Image-Based Measurements of Human Medial Gastrocnemius Muscle Fascicle Length and Pennation

Abstract: Ultrasound imaging is often used to measure muscle fascicle lengths and pennation angles in human muscles in vivo. Theoretically the most accurate measurements are made when the transducer is oriented so that the image plane aligns with muscle fascicles and, for measurements of pennation, when the image plane also intersects the aponeuroses perpendicularly. However this orientation is difficult to achieve and usually there is some degree of misalignment. Here, we used simulated ultrasound images based on three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Misalignment of the ultrasound probe with the plane of the fascicles has been shown to result in errors in fascicle length measures (0.4mm per degree of misalignment) using T-US (Bolsterlee et al, 2016). On average, ultrasound images taken of the medial gastrocnemius muscle were found to be misaligned with the fascicles by 5.5° (Bolsterlee et al, 2016; Bolsterlee et al, 2015) indicating an average error of 2.2mm; this error is comparable to the absolute error observed in our phantom measurements (2.2±1.3mm). Our study demonstrates that probe misalignment during EFOV-US does not yield significantly higher error than in T-US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misalignment of the ultrasound probe with the plane of the fascicles has been shown to result in errors in fascicle length measures (0.4mm per degree of misalignment) using T-US (Bolsterlee et al, 2016). On average, ultrasound images taken of the medial gastrocnemius muscle were found to be misaligned with the fascicles by 5.5° (Bolsterlee et al, 2016; Bolsterlee et al, 2015) indicating an average error of 2.2mm; this error is comparable to the absolute error observed in our phantom measurements (2.2±1.3mm). Our study demonstrates that probe misalignment during EFOV-US does not yield significantly higher error than in T-US.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, EFOV-US provides a novel opportunity to study forearm muscles in vivo . However, misalignment of the ultrasound probe from the plane of the fascicles has been shown to result in fascicle length error using T-US (Bolsterlee et al, 2016; Klimstra et al, 2007). Because EFOV-US requires dynamic scans over extended distances, there is concern such misalignment error could aggregate, reducing accuracy and reliability (Cronin and Lichtwark, 2013; Noorkoiv et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These include: (1) misalignment in the orientation of the ultrasound transducer may have occurred, which could result in potential errors measuring fascicle length and pennation angle (Bolsterlee et al. ); (2) differences in experimental set up (e.g., differences in knee joint angle); (3) differences in how fascicle lengths are defined (i.e., whether fascicle length was considered as the straight line distance between the insertions to the aponeuroses (Herbert et al. ), or as the length projected onto the long axis of the muscle (Herbert et al.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps a combination of several methodological differences between studies may explain the minor observed differences in fascicle contributions to muscletendon lengthening between studies. These include: (1) misalignment in the orientation of the ultrasound transducer may have occurred, which could result in potential errors measuring fascicle length and pennation angle (Bolsterlee et al 2016); (2) differences in experimental set up (e.g., differences in knee joint angle); (3) differences in how fascicle lengths are defined (i.e., whether fascicle length was considered as the straight line distance between the insertions to the aponeuroses (Herbert et al 2002), or as the length projected onto the long axis of the muscle (Herbert et al 2015); (4) differences in methods used to estimate moment arms from joint angles; and (5) whether muscle slack lengths were included or excluded in analysis of final outcomes (Herbert et al 2002(Herbert et al , 2015Hoang et al 2005;Nordez et al 2010). Given these many potential sources of variability in measurement, the differences between studies are surprisingly small.…”
Section: Discussionmentioning
confidence: 99%
“…We highlight that ultrasound estimates of pennation angles using this method are typically overestimated (Bolsterlee et al . ) but we present pennation angles to allow comparison with previously reported values using the same method (McGill et al . ; Harriss & Brown, ).…”
Section: Methodsmentioning
confidence: 97%